How does psychological resilience influence subjective career success of Internet marketers in china? A moderated mediation model - Wang, Ting; Gao, Di (Frontiers in Psychology, 2022)
In this study, the research objective of psychological resilience refers to the emerging professional group of Internet marketers under the background of the COVID-19 pandemic environment. This study uses qualitative and quantitative analyses as well as normative and empirical analyses as comprehensive research methods. This study starts from the perspective of positive psychology to investigate the psychological resilience of Internet marketers and broadens the scope of application of positive organizational behavior and psychology. The study results show that the resilience quality stimulated by adversity and chaotic life trajectory can first bring sustainable development to the professional group and then better job performance and bottom line benefits.